Dari puisi ke layar: Kritik sosial dalam film seribu kunang kunang di Jakarta - Firmansyah, Akhmad (Maliki Interdisciplinary Journal, 2025)
The short film Seribu Kunang-Kunang di Jakarta is an adaptation of Joko Pinurbo’s poem, transforming poetic ideas into a visual space of social critique. This study aims to identify the forms of social criticism in the film, the underlying causes of the issues depicted, and their broader social impacts. The analysis employs Alan Swingewood’s sociology of literature, which emphasizes that literary works are active social practices that both reflect and shape reality. The findings highlight three main points: first, the film represents the memory of the 1998 May tragedy through symbolic elements of trauma such as the black umbrella and the moon in the basket; second, poetic symbolism—such as the moon, fireflies, and the color black—serves as both aesthetic and ideological tools to articulate collective memory; third, the conflict between the poet and the Chinese-Indonesian girl illustrates the tension between dominant discourse and subaltern voices. Ultimately, the film functions not only as an aesthetic work but also as a symbolic resistance space, a visual archive, and a medium of social healing for silenced historical memories.